ANALISIS PENERAPAN MODEL TALKING STICK BAGI SISWA DALAM PEMBELAJARAN PPKn KELAS VII SMP NEGERI 4 KUALA MANDOR B - Pina Pina; Aminuyati Aminuyati; Thomy Sastra Atmaja (Universitas Tanjungpura, 2022)
AbstractThis study describes the application of the Talking Stick model in small group learning to complete assignments and group cooperation to understand the material in Civics subjects. This research method is descriptive qualitative. The results of this study indicate that the application of the Talking Stick model in Civics learning for Class VII SMP Negeri 4 Kuala Mandor obtained a small group completing the Civics learning task for Class VII SMP Negeri 4 Kuala Mandor B Kubu Raya Regency has been going well, this can be seen from the results of the assignment. correctly collected. time and get a good score with an average of 80. Students work together and help each other in understanding Civics learning material, it looks like cooperation in completing the tasks given by the teacher, where students in groups help each other to be able to quickly complete assignments or discussion topics delivered by the teacher.Keywords: students, cooperative learning, talking stick